Mandibular Actinomyces Infection Mimicking a Malignancy: Case Report - Gülay BULUT; Yasemin BAYRAM; Mehmet Deniz BULUT; Mehmet Fatih GARÇA; İrfan BAYRAM (Federation of Turkish Pathology Societies, 2017)
Actinomycosis is a rare, chronic, suppurative and granulomatous disease caused by Actinomyces israelii, which is a filamentous, anaerobic, gram-positive, saprophytic organism in the oral cavity. Diagnosis of actinomycosis depends on positive culture or identification of Actinomyces colonies and sulfur granules in histological specimens. In our case, a mass had been growing in the mandible for eight months. The mass appeared to be malignant, both clinically and radiologically. A histopathological examination of the mandible revealed actinomycosis. It should be noted that actinomycosis can mimic a malignancy, and for differential diagnosis, bone biopsy or fine-needle aspiration should be performed pre-operatively.